Pengaruh Lokasi, Store Atmosphere, dan Content Marketing Terhadap Keputusan Pembelian Konsumen Generasi Z Pada Hakui Kopi 0 KM Tulungagung - Feriyana Putri Ramadania; Rafikhein Novia Ayuanti; Agung Pambudi Mahaputra (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to determine the effect of location, store atmosphere, and content marketing on Generation Z consumer purchasing decisions at Hakui Kopi 0 KM Tulungagung. This type of research uses quantitative research with associative methods. Sampling was carried out using purposive sampling method, the population in this study were generation z consumers at Hakui Kopi 0 KM Tulungagung. The data used in this study are primary data using a questionnaire and get a sample size of 144 which can be obtained using Hair's formula. The analysis technique used in this study consists of validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test, and determination coefficient test (R2). The results of the study indicate that partially the location has a positive and significant effect on purchasing decisions with a significance value of 0.000> 0.05. Furthermore, Store Atmosphere partially has a positive and significant effect on Purchasing Decisions with a significance value of 0.000 <0.05. Content Marketing has a positive and significant effect on Purchasing Decisions with a significance value of 0.000> 0.05. The influence of Location, Store Atmosphere, and Content Marketing simultaneously has a positive and significant effect on Generation Z Consumer Purchasing Decisions at Hakui Kopi 0 KM Tulungagung.